2004
DOI: 10.1007/s00213-004-2006-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine response to intravenous citalopram in healthy control subjects: pharmacokinetic influences

Abstract: The parenteral citalopram challenge test is characterized by a modest concentration-response relationship, with concentration influenced by variable PK factors. Accounting for individual differences in drug distribution may improve the power of the citalopram challenge test, when used as an in vivo measure of central 5-HT function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…Lotrich et al (2005) (Figure 3) reported a mean plasma citalopram concentration of circa 10 ng/mL between 45 and 150 mins after an infusion of 10 mg citalopram in healthy control subjects. Meyer et al (2004) (Figure 1) measured a striatal SERT occupancy of about 50% for a plasma citalopram concentration of 10 ng/mL in subjects who had received daily oral doses of citalopram for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lotrich et al (2005) (Figure 3) reported a mean plasma citalopram concentration of circa 10 ng/mL between 45 and 150 mins after an infusion of 10 mg citalopram in healthy control subjects. Meyer et al (2004) (Figure 1) measured a striatal SERT occupancy of about 50% for a plasma citalopram concentration of 10 ng/mL in subjects who had received daily oral doses of citalopram for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The dose and timing of the injection were based on previous studies showing robust and sustained effects of this dose of citalopram on anterior pituitary hormones-a putative marker of serotonergic system integrity (Attenburrow et al, 2001;Bhagwagar et al, 2002). As published by Lotrich et al (2005) (Figure 3), this schedule leads in healthy control subjects to a fairly stable citalopram plasma concentration of about 10 ng/mL between 45 and 150 mins after the start of the infusion with little between-subject variability.…”
Section: Subjects and Medicationmentioning
confidence: 99%
“…Stimulation of hypothalamic 5-HT receptors promotes the pituitary release of prolactin, and citalopram increases serotonergic neurotransmission by highly selective inhibition of 5-HT reuptake. 14 The increase in circulating prolactin concentration induced by citalopram is dose-dependent 15 and provides an index of net serotonergic responsivity in the hypothalamic-pituitary axis. 3 Individual differences in prolactin response to serotonergic challenge are reasonably reproducible over 6 months (rϭ0.59 when menstrual cycling is controlled 16 ) and correlate across methods of assessment.…”
Section: Citalopram Challenge Testmentioning
confidence: 99%
“…Methods for determining serum prolactin and plasma citalopram concentrations have been described previously. 15 Prolactin concentrations from the two baseline prolactin samples were averaged.…”
Section: Citalopram Challenge Testmentioning
confidence: 99%
“…Healthy volunteers scoring high on depression related traits, for example, could be shown to resemble depressed patients in their responses to serotonergic stimulation by citalopram (e.g. Lotrich et al, 2005), or by clomipramine (Ruegg et al, 1997;Gerra et al, 2000). Similarly, increased cortisol responses to the noradrenaline reuptale inhibitor reboxetine in depressive healthy persons mirrored the effect of a noradrenergic challenge observed in depressed patients (Hennig et al, 2000), and a challenge by the dopamine D2 receptor agonist bromocriptine in healthy persons confirmed decreased dopaminergic activity observed in patients (Netter, 2006).…”
Section: Introductionmentioning
confidence: 77%